About Sex Among Croats: "Oh God, Let my Pride be Able" - Samaržija, Zdenko (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
Only a few streets on the outskirts of settlements in Slavonia and Baranja are named after a doctor or educator, while the central square and several streets in the centre are usually named after a patron saint, the founder of the settlement, a feudal lord or a deceased politician, with the exception of Kutjevo, which has Graševina[1] Square, and Pleternica, with its Bećarac[2] Square. However, nothing is named after the researchers of Croatian sexuality, Dr. sc. Friedrich Salom(on) Krauss, an ethnologist from Pleternica, and Dr. Ilijaš Abjanić – Jakšin, a doctor from Stari Mikanovci – there are no monuments, or at least a sign in the public space. Research on sexuality in today's neoconservative era is taboo and everything is being done to forget such scientists.[1] Welschriesling, or Italian Riesling.[2] Type of a popular genre of folk songs, usually teasing and lascivious.
Keywords: research into sex and sexual deviations; dr. sc. Friedrich Salam(on) Kraus; dr. Ilijaš Abjanić - Jakšin